Temperament profiles of Sasang typology in a child clinical sample - Soo Jin Lee; Soo Hyun Park; Han Chae (Integrative Medicine Research)
Background: Sasang typology is a personalized traditional medicine widely used in clinical diagnosis and treatment in Korea. The aim of this study was to examine the biopsychological personality profiles of traditional Korean Sasang typology in a clinical sample of Korean children. Methods: A total of 150 children were classified as one of three traditional Korean Sasang types (19 So-Yang, 118 Tae-Eum, and 13 So-Eum) by two clinical experts in Sasang typology. The childrens’ mothers completed the Korean version of the Junior Temperament and Character Inventory (JTCI). The four temperament dimensions of JTCI were compared between the different Sasang types using analysis of variance (ANOVA) and profile analysis. Results: There were no significant differences in age, gender, and parents’ education levels across the Sasang types. The JTCI temperament profile for each of the child Sasang types was significantly different (profile analysis, df = 5.315, F = 2.508, p = 0.027). There were significant differences in novelty-seeking (F = 3.850, p = 0.023) and novelty-seeking subscales, but not with other temperament dimensions. Conclusion: These results demonstrated distinct temperament traits associated with traditional Korean Sasang types in children using an objective biopsychological personality inventory. With further investigation into the biopsychological profiles of the children, the longitudinal stability of the Sasang typology can be examined.